2009
DOI: 10.1165/rcmb.2007-0456oc
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Sodium Channel Inhibition in Primary Human Bronchial Epithelia by Transfected siRNA

Abstract: Na(+) absorption and Cl(-) secretion are in equilibrium to maintain an appropriate airway surface fluid volume and ensure appropriate mucociliary clearance. In cystic fibrosis, this equilibrium is disrupted by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene resulting in the absence of functional CFTR protein, which in turn results in deficient cAMP-dependent Cl(-) secretion and predominant Na(+) absorption. It has been suggested that down-regulation of the epithelial sodium cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 28 publications
3
46
0
Order By: Relevance
“…However, the pseudostratified epithelium presents significant barriers to the delivery of nucleic acid based reagents such as plasmids (17, 65), doublestranded oligonucleotides (9,23,36,50), and single-stranded oligonucleotides (9, 23). It is evident that physical barriers, airway secretions, and host defense mechanisms (9,17,23,49,62) significantly hinder the delivery and efficacy of the siRNA reagents. The mucosal surface of the airways and the alveoli elicits immunogenic responses to RNA interference (RNAi) oligonucleotides that confound results (13,31,35,45,54), and some animal studies attempting to deliver siRNAs to the respiratory tract have reported little efficacy (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the pseudostratified epithelium presents significant barriers to the delivery of nucleic acid based reagents such as plasmids (17, 65), doublestranded oligonucleotides (9,23,36,50), and single-stranded oligonucleotides (9, 23). It is evident that physical barriers, airway secretions, and host defense mechanisms (9,17,23,49,62) significantly hinder the delivery and efficacy of the siRNA reagents. The mucosal surface of the airways and the alveoli elicits immunogenic responses to RNA interference (RNAi) oligonucleotides that confound results (13,31,35,45,54), and some animal studies attempting to deliver siRNAs to the respiratory tract have reported little efficacy (23).…”
mentioning
confidence: 99%
“…However, the pseudostratified epithelium presents significant barriers to the delivery of nucleic acid based reagents such as plasmids (17, 65), doublestranded oligonucleotides (9,23,36,50), and single-stranded oligonucleotides (9, 23). It is evident that physical barriers, airway secretions, and host defense mechanisms (9,17,23,49,62) significantly hinder the delivery and efficacy of the siRNA reagents.…”
mentioning
confidence: 99%
“…This is carried out by small sequences of 20 to 22 bases called Small-interfering RNA (siRNA) that are complementary to the target mRNA. Caci et al [34] showed this approach to be useful in inhibiting the mRNA for all 3 ENaC subunits leading to significant reduction in number of functional ENaC on respiratoary epithelium, thereby impacting fluid absorption. Further, Clark et al [35] reported the effectiveness of GSK2225745, which was designed as a siRNA targeting the alpha subunit of ENaC channel in primary cell assays, but initial attempts at delivering this oligonucleotide in the lungs or nasal cavities of mice did not show any significant change in ENaC function.…”
Section: Activation Of Purinergic Receptors -Denufosolmentioning
confidence: 99%
“…The channel is also thought to play an important role in cell volume regulation (Caci et al, 2009). ENaC channel plays crucial Table I.…”
Section: Sodium Channels Epithelial Sodium Channel (Enac)mentioning
confidence: 99%